Radical Sufficiency : Work, Livelihood, and a US Catholic Economic Ethic - Hinze, Christine Firer (Book collections on Project MUSE., 2021)
"A hallmark of the modern Catholic social tradition has been its insistence that the economy provide access to material sufficiency for all members of society, typically through fairly paid work. In the United States, the Catholic livelihood agenda found its most famous champion in Monsignor John A. Ryan (1869-1945), whose life and work straddled the reformist ferment of the Progressive era through the New Deal years. Ryan articulated a persuasive agenda for employment justice to be achieved through private and public action. Radical Sufficiency offers a Catholic social and ethical examination, critique, and rethinking for 21st century circumstances of Ryan and U.S. Catholic social teaching's agenda for worker justice. The book places that agenda within a normative understanding of a good livelihood and describes its implications for contemporary economic policy and practice. In particular, the book outlines the features of a critical Catholic economic ethic capable of illumining and addressing the situations of workers and families in the global economy of the twenty-first century. Hinze identifies transformative strategies and policy directions for pursuing the radical Christian goal of economic sufficiency for all."--